THE USE OF CRYPTOGRAPHY AS AN EDUCATIONAL TOOL - Brum, Valéria C.; Borges, Igor Godoy (Seven Editora, 2025)
This article discusses the application of an innovative teaching sequence on cryptography with class 312 at Colégio Estadual Coronel Pilar de Santa Maria, and its relationship with mathematics. We sought to develop activities using mathematical concepts such as matrix operations, inverse matrices, determinants, and modular arithmetic. The growing relevance of cryptography in the contemporary digital world motivates the need for its inclusion in school curricula, preparing students for the challenges of information security. The central objective is to make the concept of cryptography accessible and stimulating for students, promoting the development of critical thinking and problem-solving skills. DOI: https://doi.org/10.56238/sevened2025.038-072